2020
DOI: 10.1111/ane.13231
|View full text |Cite
|
Sign up to set email alerts
|

Valproate risk form—Surveying 215 clinicians involving 4775 encounters

Abstract: Objectives: Annual completion of a Valproate Risk Acknowledgement Form (RAF) is mandated in the United Kingdom due to neurodevelopmental risks of in utero valproate exposure. The number of women of childbearing potential taking valproate, the uptake of the RAF within this population and their clinical outcomes is not known or monitored. This study surveyed responses of clinicians administering the RAF to women of childbearing potential taking valproate medications. Materials and Methods: Study design-nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The main limitation of our study is its relatively small sample size. Even so, our results are in line with those of other studies based on larger samples [18][19][20][21][22][23][24][25][26][27][28] and we believe that our sample is representative of day-to-day clinical practice in the epilepsy department of a secondary healthcare centre. Another possible limitation is the relatively short follow-up period: 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…The main limitation of our study is its relatively small sample size. Even so, our results are in line with those of other studies based on larger samples [18][19][20][21][22][23][24][25][26][27][28] and we believe that our sample is representative of day-to-day clinical practice in the epilepsy department of a secondary healthcare centre. Another possible limitation is the relatively short follow-up period: 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…27 Furthermore, in a study conducted in the United Kingdom, clinicians were surveyed to monitor the use of risk acknowledgement forms with sodium valproate therapy, one year after the valproate risk acknowledgement form was implemented by the Medicines Healthcare products Regulatory Agency. 28 Lamotrigine followed by levetiracetam was the most frequently prescribed antiepileptic replacing valproate. The risk acknowledgement form for WOCBA without intellectual disability reflected that 43.5% clinicians reported that ‘most’ of their patients continued with valproate, while an additional 25.0% reported that ‘all’ of their patients continued with valproate.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive risks of VPA have to be weighed against the need for optimal seizure control. Early reports of the SANAD II study suggest that levetiracetam may be an inferior antiepileptic to VPA [41], while Angus-Leppan and colleagues found that between 33 and 43% of clinicians surveyed in the UK noted deterioration in among women who were switched from VPA to an alternative agent [42]. The risks of inadequate seizure control during pregnancy, both to the woman and the foetus, are significant and include maternal death, sudden unexpected death, small for gestational age, and preterm delivery [43].…”
Section: Discussionmentioning
confidence: 99%